Effectiveness of Probiotic for Primary Prevention of Clostridium difficile Infection: A Single-Center Before-and-After Quality Improvement Intervention at a Tertiary-Care Medical Center. (26th April 2018) - Trick, William E.; Sokalski, Stephen J.; Johnson, Stuart; Bunnell, Kristen L.; Levato, Joseph; Ray, Michael J.; Weinstein, Robert A.
Abstract : OBJECTIVE: To evaluate probiotics for the primary prevention of Clostridium difficile infection (CDI) among hospital inpatients. DESIGN: A before-and-after quality improvement intervention comparing 12-month baseline and intervention periods. SETTING: A 694-bed teaching hospital. INTERVENTION: We administered a multispecies probiotic comprising L. acidophilus (CL1285), L. casei (LBC80R), and L. rhamnosus (CLR2) to eligible antibiotic recipients within 12 hours of initial antibiotic receipt through 5 days after final dose. We excluded (1) all patients on neonatal, pediatric and oncology wards; (2) all individuals receiving perioperative prophylactic antibiotic recipients; (3) all those restricted from oral intake; and (4) those with pancreatitis, leukopenia, or posttransplant. We defined CDI by symptoms plus C. difficile toxin detection by polymerase chain reaction. Our primary outcome was hospital-onset CDI incidence on eligible hospital units, analyzed using segmented regression. RESULTS: The study included 251 CDI episodes among 360, 016 patient days during the baseline and intervention periods, and the incidence rate was 7.0 per 10, 000 patient days. The incidence rate was similar during baseline and intervention periods (6.9 vs 7.0 per 10, 000 patient days; P =.95). However, compared to the first 6 months of the intervention, we detected a significant decrease in CDI during the final 6 months (incidence rate ratio, 0.6; 95% confidence interval, 0.4–0.9; P =.009). Testing intensity remained stable between the baseline and intervention periods: 19% versus 20% of stools tested were C. difficile positive by PCR, respectively. From medical record reviews, only 26% of eligible patients received a probiotic per the protocol. CONCLUSIONS: Despite poor adherence to the protocol, there was a reduction in the incidence of CDI during the intervention, which was delayed 6 months after introducing probiotic for primary prevention. Infect Control Hosp Epidemiol 2018;765–770